PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT MANDIRI CIPTA SEJAHTERA - Nugroho, Aditya; Utama, Rony Edward (Taksasila Edukasi Insani, 2024)
Employee performance is very important for the progress of a company. The aim of this research is to determine the effect of compensation and work environment on employee performance by taking a case study at PT Mandiri Cipta Sejahtera. Researchers took a sample of 50 respondents. The research method used is a quantitative method with associative research using primary data. The results of this research indicate that the Compensation variable has a positive and significant effect on PT Employee Performance. Mandiri Cipta Sejahtera (X1) with a calculated t value greater than t table (3.042 2.011) and a significance level (0.004 0.05), the Work Environment has a positive and significant effect on PT Employee Performance. Mandiri Cipta Sejahtera (X2) with a calculated t value greater than t table (3.420 2.011) and a significance level (0.001 0.05) as well as Compensation and Work Environment together have a significant effect on PT Employee Performance. Mandiri Cipta Sejahtera (Y) with a calculated F value greater than F table (23.384 3.20) and significance level (0.00 0.05). Keywords : Compensation; Work environment; Employee performance